PELATIHAN PENGUKURAN ANTROPOMETRI PADA KADER POS BINAAN TERPADU PENYAKIT TIDAK MENULAR (POSBINDU PTM) - Mutalazimah Mutalazimah; Dyah Intan Puspitasari (Universitas Muhammadiyah Surakarta, 2026)
According to data from the community health center, two of the top three diseases in Prambanan District are non-communicable diseases (NCDs): hypertension (32.63%), the common cold (25.61%), and diabetes mellitus (DM) (19.03%). Based on the principles of community-based health efforts, the community must be able to perform anthropometric measurements to enable early detection of NCD risk. This community service activity aimed to provide anthropometric measurement training to integrated health sevices for NCD (Posbindu PTM) cadres in Daleman Hamlet, Sumberharjo, Prambanan, Sleman. The training, attended by 13 cadres, covered the theory and practice of anthropometric measurements related to NCDs, including weight, height, mid-upper arm circumference (MUAC), waist circumference, and hip circumference. Improvements in knowledge and skills were observed after the training, as evidenced by the correct use of measurement procedures. The training is expected to increase the cadres' confidence in providing anthropometric measurements to the community.